2019
DOI: 10.1007/jhep02(2019)177
|View full text |Cite
|
Sign up to set email alerts
|

Vcb determination from inclusive b → c decays: an alternative method

Abstract: The determination of V cb relies on the Heavy-Quark Expansion and the extraction of the non-perturbative matrix elements from inclusive b → c decays. The proliferation of these matrix elements complicates their extraction at 1/m 4 b and higher, thereby limiting the V cb extraction. Reparametrization invariance links different operators in the Heavy-Quark expansion thus reducing the number of independent operators at 1/m 4 b to eight for the total rate. We show that this reduction also holds for spectral moment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 49 publications
0
72
0
Order By: Relevance
“…In Refs. [326,331] it has been shown that the number of independent parameters in higher orders can be reduced by reparametrization invariance, for the total rate and the q 2 moments. While the number of HQE parameters up to order 1/m 2 b is still two, there is only one parameter at 1/m 3 b , since the spin-orbit term can be absorbed into μ 2 G .…”
Section: Higher Power Correctionsmentioning
confidence: 99%
“…In Refs. [326,331] it has been shown that the number of independent parameters in higher orders can be reduced by reparametrization invariance, for the total rate and the q 2 moments. While the number of HQE parameters up to order 1/m 2 b is still two, there is only one parameter at 1/m 3 b , since the spin-orbit term can be absorbed into μ 2 G .…”
Section: Higher Power Correctionsmentioning
confidence: 99%
“…However, parametrically this correction is of the same size as the yet unknown corrections of order α 2 s Λ 2 QCD =m 2 b and α 3 s , which would need to be included in a full analysis up to order α s Λ 3 QCD =m 3 b . We note in passing that the corrections α s ρ 2 LS are not needed, since these are included in the known α s μ 2 G contributions [41]. Nevertheless, the contribution of ρ D is significant due to the large coefficient in front of ρ D and hence we expect that the impact of this correction is the largest one.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, we derived the total rate and spectral moments up to 1/m 4 c , and defined three new parameters that contain four-quark (weak annihilation) operators. We emphasize, that RPI observables, such as the total rate and q 2 moments, depend on a reduced set of HQE parameters [14]. Therefore, it may be useful to do an experimental analysis using q 2 moments only, as this significantly reduces the number of free parameters.…”
Section: Discussionmentioning
confidence: 99%
“…We emphasize that total rate only depends on τ 0 , while the RPI q 2 moments additionally depend on τ m . As was pointed out in [13,14], the q 2 moments have the advantage that they depend on a reduced set of 10 operators, even when including the terms up to 1/m 4 c . For the non-RPI energy moments, additional matrix elements (up to 16) have to be introduced.…”
Section: A New Set Of Hqe Parametersmentioning
confidence: 96%
See 1 more Smart Citation